STUDI KARAKTERISTIK TANAH RESIDUAL VULKANIK BERDASARKAN SIFAT MAGNETIK DAN SIFAT KETEKNIKAN TANAH - Faridlah, Mela (2016)
Penelitianmengenaikarakteristiktanah residual vulkanikmenggunakanmetodemagnetikdanmetodeketeknikantelahdilakukanpadalerengstabildanlerenglongsor yang berada di DesaLangensariKecamatanLembangKabupaten Bandung BaratProvinsiJawa Barat.Penelitianinidimaksudkanuntukmengetahuigambarankarakteristiksuseptibilitasmagnetikdan parameter keteknikantanah residual vulkanik.Karakteristikketeknikanditentukanmelaluiujifisikberupaujibobotisi, beratisitanahbasah, beratisitanahkering, kadar air, derajatkejenuhandanporositas, ujibatasatterbergsertaujiukuranbutirtanah..KarakteristikmagnetikditentukanmelaluiujisuseptibilitasmagnetikmenggunakanBartington MS2B (MagneticSuseptibility System sensor B) dual frekuensiyaitu 470 Hz dan 4,7 kHz. Hasilpenelitianinimenunjukkanpeningkatannilai-nilaiχLF (suseptibilitasfrekuensirendah) danχFD% (suseptibilitasbergantungfrekuensi)kearah horizon bagianatasprofiltanah residual. Peningkatannilai-nilaiχLFdanχFD% kearah horizon bagianatasmerupakankarakteristikdarisuseptibilitasmagnetik.Dari hasil penelitian geoteknik dan magnetik didapatkan hasil jenis tanah residual vulkaniktersebutmerupakantanahlempungdengan mineral dominanyaituHematite.Hubunganantara parameter magnetik danketeknikantanahyaitubeberapa parameter keteknikan yang mempengaruhisifatkemagnetandiantaranyaberatisitanahbasahdankadar air;-- Research on volcanic residual soil characteristics using magnetic methods and geotechnic methods was carried out on a stable slope and landslide slope are located in LangensariLembang west Bandung, West Java Province. This study are intended to describe the characteristics of the magnetic susceptibility and residual volcanic soil engineering parameters. Geotechnical characteristics were determined by physical properties tests such as bulk density test, wet density, dry density, water content, degree of saturation and porosity, atterberg limit test and grain size distribution test. Magnetic characteristics were determined by magnetic suseptibility test using Bartington MS2B (Magnetic Suseptibility System sensor B) dual frequency are 470 Hz and 4,7 kHz. This research show the increased of value of χLF (low frequency susceptibility) andχFD% (frequency dependent susceptibility) towards the upper horizon of the residual soil profile. The increase of the value of χLFdanχFD% towards the upper horizon is the characteristic of magnetic susceptibility. The result of this research shows that the type of the volcanic residual soil is clay with Hematite as the dominant mineral.Relation between magnetic parameter and geotechnical parameter is some geothecnicalparameters influence magnetic properties are wet density and water content.